Evaluation of Employee’s Performance in the Jordanian and Emeriti Laws: A Comparative Study - Elyat, Mohammad Njim Ibrahim (Dirasat: Shari’a and Law Sciences, 2020)
The public administration resorts to evaluating the performance of public employees periodically, through performance evaluation reports, whether annual, semi-annual, or quarterly, and these reports, after gaining the categorical degree, have important implications, both for the public administration and for the public employee alike, and the legislator has resorted to briefing these reports with many guarantees to achieve their goals. To have a complete and clear picture of performance evaluation in the Jordanian and Emirati legal system, the study followed the comparative legal approach, using the descriptive and analytical research method for the relevant legal texts. After highlighting the evaluation of job performance in both Jordanian and Emirati law, the study reached a set of the following conclusions and recommendations. The Jordanian legislator did not authorize the grievance from the performance reports except when the estimate is (weak), and the Emirati legislator did not authorize the grievance from the performance reports only when the estimate is (needs to be improved). this means that an employee who receives a (very good), (good), or (average) rating in Jordanian law and(exceeds expectations) or (meets expectations) cannot complain about it. The researcher recommended the need to call on the legislator in both Jordan and the UAE to provide for the need to grant the employee a guarantee in complaining about job performance evaluation reports